2009
DOI: 10.1021/bm901109z
|View full text |Cite
|
Sign up to set email alerts
|

Functional Cycloamylose as a Polysaccharide-Based Biomaterial: Application in a Gene Delivery System

Abstract: Cycloamylose (CA) exhibits differences in geometry and greater colloidal stability compared with amylose. Here we report the synthesis of a cationic CA derivative and its application for gene delivery. Cationic CA (catCA) and cationic amylose (catAmy) were synthesized by introducing spermine groups. The interactions between catCA or catAmy with plasmid DNA encoding firefly luciferase was examined by gel electrophoresis, dynamic light scattering, and transmission electron microscopy. Activity as a gene delivery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
45
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 30 publications
0
45
0
Order By: Relevance
“…Hyperbranched cationic glycogen derivatives as efficient gene vectors the DMAPA-Glyp/pDNA and the AEPZ-Glyp/pDNA complexes, respectively (lanes [3][4][5][6][7][8][9][10][11][12][13][14]. This demonstrated that the glycogen derivatives exhibited distinct protective effects against DNase I.…”
mentioning
confidence: 85%
See 4 more Smart Citations
“…Hyperbranched cationic glycogen derivatives as efficient gene vectors the DMAPA-Glyp/pDNA and the AEPZ-Glyp/pDNA complexes, respectively (lanes [3][4][5][6][7][8][9][10][11][12][13][14]. This demonstrated that the glycogen derivatives exhibited distinct protective effects against DNase I.…”
mentioning
confidence: 85%
“…3,12 Glycogen (0.62 mmol glucose units, 0.1000 g) was dissolved in 10 mL of anhydrous DMSO, and subsequently activated by the addition of CDI (5.58 mmol, 0.9045 g). The resulting mixture was then stirred for 1 hour in a nitrogen atmosphere at room temperature.…”
Section: Synthesis and Characterization Of Hyperbranched Cationic Glymentioning
confidence: 99%
See 3 more Smart Citations